COMPARAÇÃO ERGONÔMICA EM HARVESTER DE ESTEIRAS E PNEUS NO DESBASTE DE PINUS – ESTUDO DE CASO - Martins, Alysson Braun (2019)
The mechanized harvesting in forest stands subjected to thinning is a complex task due to reduced spaces for machine displacement, low operational productivity and high production costs, requiring constant operator attention. Such condition, coupled with long hours of work, may cause the operator occupational problems. The objective of this study was to perform a comparative ergonomic analysis at the work station of harvesters of treadmills and tires in the harvesting of wood in stands subjected to thinning. The study was carried out in stands of Pinus taeda, submitted to the first roughing with 10 years of age. The operation was evaluated using two harvesters, one with track wheels and one with tire wheels. The ergonomic analysis contemplated the environmental factors (exposure to heat, noise and vibration); postural analysis; and repetitive motions. The occupational exposure to heat, noise and vibration were evaluated according to the criteria established by NHO 06, 01 and 09 respectively. In the postural analysis, the typical postures adopted by the operators were identified, with subsequent analysis by the REBA and RULA methodologies. In the analysis of repetitiveness in the work, the repetitive movement was characterized by counting by cycle, shift and working day, analyzing by Strain Index and TOR-TOM methodologies. The results showed values of wet bulb index and globe thermometer (IBUTG) below the maximum limit established by the standard. The results of the normalized exposure level (NEN) were below the action level (58 and 62 dB). The daily dose was above the level of action on the mat harvester (52%), indicating the need for preventive measures. The results of the normalized exposure acceleration (aren) showed values above the level of action on the mat harvester (0.6m / s²) and, for the value of the resulting vibration dose (VDVR), both were above the action level (9.3 and 11.2 m / s 1.75). We identified 15 typical postures adopted by the operator in the treadmill harvester and 8 in the tire harvester, with average health risk. The repeatability analysis showed greater number of movements in the tire harvester per cycle, shift and working day, however, the machine commands are better distributed. In general, the ergonomic conditions at the tire harvester's work station were favorable when compared to the harvester of treadmills, the machine being more ergonomically appropriate for harvesting wood in stands subjected to thinning.